The Effectiveness of Learning during the Corona Pandemic - Parijem Parijem; Wakhudin Wakhudin; Subiarto Subiarto (Research and Innovation in Social Science Education Journal (RISSEJ), 2023)
This research was conducted on the basis of the author's concerns during the Corona Pandemic, especially the situation in the education sector. As an actor of education, the writer feels compelled to contribute thoughts that might be useful for education in the future. The purpose of this study was to determine the effectiveness of learning during the Corona pandemic. The research method apart from distributing questionnaires, the author also conducts documentation studies and observations in the field. The results of this study are to state that the effectiveness of learning during the Corona pandemic is currently not effective, there are still many teachers who are confused about learning during the corona pandemic. This confusion is not only due to the limited means for online learning, as well as the inadequacy of human resources to face a completely unexpected and unexpected situation so that there is no preparation at all to face the Corona pandemic. The conclusion in this study is that the effectiveness of learning during the corona pandemic has not been achieved. This is due to several factors, including: the government is not ready to provide facilities and infrastructure for online learning in all schools in Indonesia, the ability or competence of teachers who are also not ready for online learning, and uneven networks in rural schools.